Pengaruh E-resources Dan Literasi Informasi Terhadap Kompetensi Lulusan Magister (S2) - Anton Risparyanto (UNILIB : Jurnal Perpustakaan, 2023)
In order to develop and manage science and technology as well as research, the competence of Masters graduates (S2) can be increased through the availability of e-resources collections in the library and students' information literacy skills. The problem of the influence of collection of e-resources and information literacy on the competence of Master graduates (S2) needs to be done with the aim of knowing: 1) The high value of e-resources, information literacy and competence of Master graduates (S2). 2) The relationship between e-resources and information literacy and 3) The significant value and influence of e-resources and information literacy on the competence of Master graduates (S2) partially or simultaneously. This quantitative research consists of 2 independent variables, namely e-resources and information literacy with the dependent variable competence of Masters graduates (S2) with the number of samples taken by probability sampling. Data were analyzed with multiple linear regression, F test method, t test and determinant test (R2). The results of the study can be concluded that the availability of electronic resources (e-resources) has a significant relationship with information literacy skills. This relationship alone (partially) has a significant effect on making a relative contribution to the competence of Master graduates (S2). Likewise simultaneously (simultaneously) has a significant influence in making an effective contribution to the competence of Masters graduates (S2) by 13.1%.